Exclusion, inequality and rootlessness, from the experience of students from the Universidad Veracruzana, Xalapa region - Garizurieta Bernabe, Jessica (IE Revista de Investigación Educativa de la REDIECH, 2021)
In Mexico there is little relevance between curricula and the real needs of society. Due to this disparity, there have been complex transformations within the higher education system. However, the results obtained have not been optimal. The present study, with an exploratory character and from a university empirical reference of concrete public character, tries to visualize the process of exclusion, inequality and uprooting from the perspective of the students themselves. These scenarios are analyzed specifically through the methodology of life stories, counting through a platform of analysis from students of the Universidad Veracruzana, Xalapa region.